PERLINDUNGAN HUKUM BAGI PIHAK KETIGA PEMILIK ALAT ANGKUT DALAM PENGANGKUTAN KAYU ILEGAL - Irawan, Rendi Rezki (Program Magister Ilmu Hukum Universitas Ekasakti, 2018)
The cases of illegal logging beside make owners as accused also driver who bring andcarry away of illegal wood by truck or other vehicles make them as accused, becauserequested by the owners of wood where uncompleted by legal documents (SKSHH), untilthe action given punishment or criminal sanction as regulated in the Passage 50 verse (3)alphabet (h) Jo Passage 78 verse (7) Law Number 41 Year 1999 about forestry and LawNumber 18 Year 2003about Eradication of Disturber of Forestry on the Changing of LawNumber 19 Year 2014 about Forestry. The cases of illegal wood carrying away by CourtBatusangkar and Court Muaro Bungo, they are Case Number: 133/Pid.B/2012/PN.BS. danNumber: 12/Pid. B/2012/PN. Mab.)